Utilization of Zoom Application as An Online Learning Media During the Covid-19 Pandemic at Politeknik Penerbangan Indonesia Curug - Kurniawati, Zulina; Kurnianto, Benny; Abdusshomad, Alwazir; Kalbuana, Nawang; Prasetyo, Budi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The spread of covid-19 in Indonesia requires all Cadets on campus under the Ministry of Transportation in Indonesia to be conducted online. Politeknik Penerbangan Indonesia Curug is one of the schools under the Ministry of Transportation that applies in the Covid-19 epidemic to online learning through the Zoom application. Zoom.us provides a version of Zoom Education as a form of CSR provided to schools affected by the Covid-19 Pandemic. Online learning’s effectiveness is very important, so cadets understand the lessons during the Teaching and Learning Activities (KBM). This study aims to understand how effective online learning is conducted at Politeknik Penerbangan Indonesia Curug using the Zoom application. This research uses a qualitative research method and data collection techniques by conducting interview techniques. This research resulted in online learning conducted with a zoom application at Politeknik Penerbangan Indonesia Curug. Online learning got an excellent response from cadets because it offered greater flexibility in their studies. Online learning makes cadets more independent but also encourages cadets more active when learning. In addition, acceptance and the understanding delivered by lecturers can be felt by the Cadets at Politeknik Penerbangan Indonesia Curug. But this online learning system also has weaknesses: limited cadets quota, which causes not all cadets to go online by activating the video so that lecturers cannot see all activities carried out by cadets.